Green Accounting and its Role in Developing Countries like India (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Green Accounting is the route that's observed towards the low-cost future. The supported diploma of pay that is achieved without draining the Natural Assets of the Nation is through Green Accounting. Whenever the Economic Damages are taken into consideration as for the fatigue of Natural Resources even as deciding the Income of the country it's miles referred to as Green Accounting. The principle objective of the review is to comprehend the pretended by Green bookkeeping in the advancement of the Indian Economy and furthermore its goals, stages, structure, need and difficulties. System of the paper depends on the optional sources regarding the pretended by green bookkeeping in creating India. The paper is an applied exploration paper. Readiness of embracing green bookkeeping isn't sufficient, it should be done likewise. Information in regards to the significance of green bookkeeping isn't sufficient, should be applied in the filling in also. Simply the direness of doing isn't adequate; everything should be brought right into it too.